2016
DOI: 10.1093/qjmed/hcw026
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection is associated with an increase in systolic blood pressure in older individuals

Abstract: Background: Cytomegalovirus (CMV) is a chronic infection that is widely distributed in the population. CMV infects a range of tissues, including endothelium, and viral replication is suppressed by the host immune system. Infection is associated with increased risk of mortality from vascular disease in older people, but the mechanisms behind this have not been determined.Aim: We investigated the association between CMV infection and cardiovascular phenotype in a cohort of healthy elderly donors.Design: CMV sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
2
30
2
1
Order By: Relevance
“…Further studies have implicated chronic HCMV infection as a risk factor for cardiovascular disease (CVD); a recent meta-analysis of studies conducted in HICs, estimated a 22% increased relative risk of CVD with exposure to HCMV [ 13 ]. In a UK setting, HCMV infection was associated with the development of arteriosclerosis [ 14 ] and a 3mmHg increase in systolic blood pressure among older individuals [ 15 ]. As Africa undergoes what has been described as an ‘epidemiological shift’ from infectious to non-communicable disease [ 16 ], an estimated 1.2 million deaths in Africa were attributed to CVD in 2004 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have implicated chronic HCMV infection as a risk factor for cardiovascular disease (CVD); a recent meta-analysis of studies conducted in HICs, estimated a 22% increased relative risk of CVD with exposure to HCMV [ 13 ]. In a UK setting, HCMV infection was associated with the development of arteriosclerosis [ 14 ] and a 3mmHg increase in systolic blood pressure among older individuals [ 15 ]. As Africa undergoes what has been described as an ‘epidemiological shift’ from infectious to non-communicable disease [ 16 ], an estimated 1.2 million deaths in Africa were attributed to CVD in 2004 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings also call for additional research into the interaction of CMV with other, non-immune health risks such as mood (depression, anxiety; Phillips, Carroll, Khan, & Moss, 2008) or hypertension (Firth et al, 2016) in the promotion of immune senescence. In the present sample, individuals without either CMV or beta-blockers had the best antibody persistence.…”
Section: Discussionmentioning
confidence: 94%
“…24 Also, we found a significant prevalence in the number of copies of cytomegaloviral DNA in patients who were older and hypertensive, which corresponds to the previous studies that showed the positive correlation of antibodies to cytomegalovirus and cytomegaloviral microRNA with arterial blood pressure, especially in older patients. 38,67,68 Moreover, one of the possible mechanisms of the development of hypertension in patients with cytomegalovirus infection could also be the development of endothelial dysfunction with the synthesis of proinflammatory cytokines and renin by endothelial cells infected with cytomegalovirus. 69 Endothelial function plays an important role in patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%